MAPPING OF COVID-19 VACCINATION RECIPIENTS IN SUKOHARJO REGENCY BASED ON WEBGIS - Ihsan Cahyo Utomo; Umi Fadlilah (Jurnal Teknik Informatika (Jutif), 2022)
Corona Virus Disease 19 (Covid-19) is an infectious disease caused by the acute respiratory syndrome coronavirus 2 (SARS-CoV-2). One of the efforts of the World Health Organization (WHO) in breaking the chain of the spread of Covid-19 is to implement health protocols and implement the Covid-19 vaccine program. Indonesia is one of the countries that implements the Covid-19 vaccination program in order to break the chain of the spread of Covid-19. Based on data from the Ministry of Health of the Republic of Indonesia on November 23, 2021, a total of 135,716,042 vaccinations were recorded for dose 1 and 90,520,201 for dose 2. To assist medical officers in determining vaccination targets and providing information to the public, a system that provides an overview is needed. mapping of vaccination recipients in the Sukoharjo area. In this study, a website-based mapping system was designed using webGIS, the data processed were data on the location and number of vaccine recipients based on age groups in the Sukoharjo Regency area. In designing the system using the Unifield Modeling language (UML) method to describe the design of the system being built. This application is made using the PHP and MySql programming languages ​​to manage the database. Testing is done using the blackbox method by testing the features of the resulting application. The result of this study is a WebGIS-based map of the distribution of the COVID-19 vaccination which contains information on the number of vaccination recipients per sub-district in the Sukoharjo Regency area.